Seeing eye to eye: trustworthy embodiment for task-based conversational agents - Robb, David A.; Lopes, José; Ahmad, Muneeb I.; McKenna, Peter E.; Liu, Xingkun; Lohan, Katrin; Hastie, Helen (Frontiers in Robotics and AI, 2023)
Smart speakers and conversational agents have been accepted into our homes for a number of tasks such as playing music, interfacing with the internet of things, and more recently general chit-chat. However, they have been less readily accepted in our workplaces. This may be due to data privacy and security concerns that exist with commercially available smart speakers.However, one of the reasons for this may be that a smart speaker is simply too abstract and does not portray the social cues associated with a trustworthy work colleague. Here, we present an in-depth mixed methods study, in which we investigate this question of embodiment in a serious task-based work scenario of a first responder team. We explore the concepts of trust, engagement, cognitive load and human performance using a humanoid head style Robot, a commercially available Smart speaker and a specially developed dialogue manager. Studying the effect of embodiment on trust, being a highly subjective and multi-faceted phenomena, is clearly challenging and our results indicate that potentially the Robot, with its anthropomorphic facial features, expressions and eye-gaze, was trusted more than the Smart Speaker. In addition, we found that embodying a conversational agent helped increase task engagement and performance compared to the Smart Speaker. This study indicates that embodiment could potentially be useful for transitioning conversational agents into the workplace and future in-situ, "in the wild" experiments with domain workers could be done to confirm this.